2013
DOI: 10.1007/s00280-013-2122-0
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study of intraperitoneal docetaxel plus S-1 for the gastric cancer patients with peritoneal carcinomatosis

Abstract: PurposeWe designed a phase I/II trial of intraperitoneal (IP) docetaxel plus S-1 to determine the maximum tolerated dose (MTD) and recommended dose (RD) and to evaluate its efficacy and safety in gastric cancer patients with peritoneal carcinomatosis (PC).MethodsPatients with PC confirmed by laparoscopy or laparotomy received IP docetaxel on days 1 and 15 and S-1 (80 mg/m2) on days 1–14 every 4 weeks.ResultsIn the phase I part (n = 12), each cohort received escalating doses of docetaxel (35–50 mg/m2); the MTD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 30 publications
1
72
3
Order By: Relevance
“…These combinations may be particularly effective for patients with small volumes of disease and symptomatic ascites. A phase I/II trial revealed that IP docetaxel plusS-1 was safe and effective in patients with gastric cancer with PC (30). The present study analyzed the effectiveness of a combination of systemic chemotherapy (intravenous docetaxel) and loco-regional chemotherapy (IP CDDP), with the two administered on day 1 of every 3-week cycle.…”
Section: Discussionmentioning
confidence: 99%
“…These combinations may be particularly effective for patients with small volumes of disease and symptomatic ascites. A phase I/II trial revealed that IP docetaxel plusS-1 was safe and effective in patients with gastric cancer with PC (30). The present study analyzed the effectiveness of a combination of systemic chemotherapy (intravenous docetaxel) and loco-regional chemotherapy (IP CDDP), with the two administered on day 1 of every 3-week cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In a Phase I/II study of intraperitoneal docetaxel and S1 by Fushida et al, they showed that 52% of patients had peritoneal disease that responded to the chemotherapy [93]. 11% was complete response while 41% was partial response.…”
Section: Discussionmentioning
confidence: 99%
“…In these trials, only patients who had a response to bi-directional chemotherapy went on to have surgery. This ranged from 53% to 85% [35,42,[92][93][94]. 65-70.7% of patients had complete cytoreduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, taxanes, such as paclitaxel (PTX) or docetaxel (DOC), are supposed to be ideal drugs for IP chemotherapy because of high local concentrations over a long period of time due to their hydrophobic properties [10]. In fact, we and others have recently shown that IP administration of PTX or DOC can exhibit remarkable effects against PM from gastric cancer (GC) [11][12][13][14]. However, the underlying mechanism to explain the marked shrinkage of PM is still unknown.…”
Section: Introductionmentioning
confidence: 99%